Biomechatronic design and control of an anthropomorphic artificial hand for prosthetic applications. Issue 10 (23rd January 2015) - Zhang, Ting; Wang, Xin Qing; Jiang, Li; Wu, Xinyu; Feng, Wei; Zhou, Dingjiang; Liu, Hong
SUMMARY: In this paper, we propose a biomechatronic design of an anthropomorphic artificial hand that is able to mimic the natural motion of human fingers. The prosthetic hand has 5 fingers and 15 joints, which are actuated by 5 embedded motors. Each finger has three phalanges that can fulfill flexion-extension movements independently. The thumb is specially designed to move along a cone surface when grasping, and the other four fingers are well developed based on the four-bar link mechanism to imitate the motion of the human finger. To accomplish the sophisticated control schemes, the fingers are equipped with numerous torque and position sensors. The mechanical parts, sensors, and motion control systems are integrated in the hand structure, and the motion of the hand can be controlled through electromyography (EMG) signals in real-time. A new concept for the sensory feedback system based on an electrical stimulator is also taken into account. The low-cost prosthetic hand is small in size (85% of the human hand), of low weight (420 g) and has a large grasp power (10 N on the fingertips), hence it has a dexterous and humanlike appearance. The performance of the prosthetic hand is validated in a clinical evaluation on transradial amputees.